CFD modelling of flow and solids distribution in carbon-in-leach tanks - Wadnerkar, Divyamaan; Pareek, V.; Utikar, R. (2015)
The Carbon-in-Leach (CIL) circuit plays an important role in the economics of a gold refinery. The circuit uses multiphase stirred tanks in series, in which problems such as dead zones, short-circuiting, and presence of unsuspended solids are detrimental to its efficiency. Therefore, the hydrodynamics of such a system is critical for improving the performance. The hydrodynamics of stirred tanks can be resolved using computational fluid dynamics (CFD). While the flow generated by the impellers in the CIL tanks is complex and modelling it in the presence of high solid concentration is challenging, advances in CFD models, such as turbulence and particle-fluid interactions, have made modelling of such flows feasible. In the present study, the hydrodynamics of CIL tanks was investigated by modelling it using CFD. The models used in the simulations were validated using experimental data at high solid loading of 40 wt. % in a lab scale tank. The models were further used for examining the flow generated by pitched blade turbine and HA-715 Mixtec impellers in lab scale CIL tanks with 50 wt. % solids. The effect of design and operating parameters such as off-bottom clearance, impeller separation, impeller speed, scale-up, and multiple-impeller configuration on flow field and solid concentrations profiles was examined. For a given impeller speed, better solids suspension is observed with dual impeller and triple impeller configurations. The results presented in the paper are useful for understanding the hydrodynamics and influence of design and operating parameters on industrial CIL tanks.